Review on the extraction of bioactive compounds and characterization of fruit industry by-products - Patra, Abhipriya; Abdullah, S.; Pradhan, Rama Chandra (Bioresources and bioprocessing, 2022)
The by-products produced from fruit processing industries could be a potential hazard to environmental pollution. However, these by-products contain several biologically active molecules (essential fatty acid, phenolic compounds, flavonoids, coloring pigments, pectin, proteins, dietary fibers, and vitamins), which can be utilized for various applications in the food, pharmaceutical, cosmetic and textile industries. Nevertheless, during extraction, these bioactive compounds' recovery must be maximized using proper extraction technologies, keeping both economy and environment under consideration. In addition, the characteristics of the extract obtained from those by-products depend mainly on the parameters considered during the extraction process. In this review, an overview of different technologies used to extract bioactive compounds from fruit industry by-products such as seeds and peels has been briefly discussed, along with their mechanisms, process, advantages, disadvantages, and process parameters. In addition, the characteristics of the extracted bioactive compounds have also been briefly discussed in this review. Graphical Abstract